Safety and immunogenicity of a third COVID-19 vaccination in patients with immune-mediated inflammatory diseases compared with healthy controls. Issue 2 (15th September 2022) - Kartnig, Felix; Mrak, Daniel; Simader, Elisabeth; Tobudic, Selma; Radner, Helga; Mandl, Peter; Göschl, Lisa; Hommer, Nikolaus; Mayer, Margareta; Hofer, Philipp; Hummel, Thomas; Deimel, Thomas; et al.
Abstract : Objectives: A third COVID-19 vaccination is recommended for immunosuppressed patients. However, data on immunogenicity and safety of a third COVID-19 vaccination in patients with immune-mediated inflammatory diseases (IMIDs) are sparse and therefore addressed within this clinical trial. Methods: 60 immunosuppressed patients and 48 healthy controls (HCs) received a third vaccination with an mRNA vaccine. The primary endpoint was defined as the presence of antibody levels against the receptor-binding domain (RBD)>1500 BAU/mL in patients with IMIDs versus HCs. Further endpoints included differences in neutralising antibodies and cellular immune responses after the third vaccination. Reactogenicity was recorded for 7 days, and safety was evaluated until week 4. Results: Rate of individuals with anti-RBD antibodies>1500 BAU/mL was not significantly different after the third vaccination between patients with IMIDs and HCs (91% vs 100% p=0.101). Anti-RBD and neutralising antibody levels were significantly lower in patients with IMIDs after the third vaccination than in HCs (p=0.002 and p=0.016, respectively). In contrast, fold increase in antibody levels between week 0 and 4 was higher in patients with IMIDs. Treatment with biological (b) disease-modifying anti-rheumatic drugs (DMARD) or combination of bDMARDs and conventional synthetic DMARDs was associated with reduced antibody levels. Enhanced cellular immune response to wild type and Omicron peptide stimulation was observed after the third vaccination. No serious adverse event was attributed to the third vaccination. Conclusion: Our clinical trial data support the immunogenicity and safety of a third COVID-19 vaccination in patients with IMIDs. However, effects of DMARD therapy on immunogenicity should be considered. Trial registration number: EudraCT No: 2021-002693-10.